The Impact of Money Laundering on Global Economic Stability and International Business: A Multidimensional Analysis - Riyan Andni (Journal of Business Crime, 2025)
Objective: This research aims to analyse the impact of money laundering on global economic stability and international business. The main focus of this research is how money laundering creates economic distortions, disrupts international financial markets, and examines the effectiveness of anti-money laundering regulations in the context of the digital economy. Research Design & Methods: This research uses a qualitative method with a multidisciplinary approach. This research examines the phenomenon of money laundering and its impact on economic stability through in-depth analysis of relevant literature as well as secondary data from reports of international institutions and case studies in various countries. Findings: The research found that money laundering has a significant impact on distorting asset prices and capital flows in international markets. In addition, the results show that existing anti-money laundering regulations are often inadequate in the face of the complexity of cross-border transactions in the digital age. Legal gaps and differences in enforcement standards across jurisdictions lead to gaps that criminals exploit to launder their money more effectively.  Implications: The findings have important implications for international policymakers and regulators. The research highlights the need for regulatory harmonization and enhanced international cooperation in anti-money laundering law enforcement. In addition, the research also emphasizes the importance of technological innovation in detecting and preventing money laundering practices in the digital economy era. Contribution: This research contributes to the literature on money laundering by offering a new perspective on the global economic impact and challenges of law enforcement in the digital age. In addition, it provides practical insights for policymakers in formulating more effective strategies to combat money laundering and protect global economic stability.